Proceedings of the 7th International Conference on Industrial Engineering (ICIE 2021) Volume II - Radionov, Andrey A.; Gasiyarov, Vadim R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book highlights recent findings in industrial, manufacturing and mechanical engineering, and provides an overview of the state of the art in these fields, mainly in Russia and Eastern Europe. A broad range of topics and issues in modern engineering is discussed, including the dynamics of machines and working processes, friction, wear and lubrication in machines, surface transport and technological machines, manufacturing engineering of industrial facilities, materials engineering, metallurgy, control systems and their industrial applications, industrial mechatronics, automation and robotics. The book gathers selected papers presented at the 7th International Conference on Industrial Engineering (ICIE), held in Sochi, Russia, in May 2021. The authors are experts in various fields of engineering, and all papers have been carefully reviewed. Given its scope, the book will be of interest to a wide readership, including mechanical and production engineers, lecturers in engineering disciplines, and engineering graduates.
Computer simulation of microprofile strain under orthogonal impact under constrained load -- Design of ultrasonic auxiliary equipment -- Reduction of vibroacoustic characteristics of generating bevel and hypoid gears -- Development of an algorithm for the airfoil profile blank part formation for compressor blades in a computer-aided design system -- Implementing the Industry 4.0 concept in the information system at the preproduction stage -- Study of the influence of ion bombardment on the quality of coatings obtained by the vacuum arc deposition -- Residual stress formation during Steel tubes expansion -- Theoretical evaluation of contact stiffness for flat rough surfaces of slide-ways with Green's function -- Subtract simulators to verify hole-making precision of control programs: an improvement in computer-aided process engineering systems -- On the influence of process parameters on the quality of the additively manufactured steel components.
Keywords: Industrial engineering; Production engineering; Machinery; Control engineering; Robotics; Automation; Industrial and Production Engineering; Machinery and Machine Elements; Control, Robotics, Automation; Industrial engineering -- Congresses; Materials -- Congresses; Production engineering -- Congresses